Adaptability of Powdered Activated Carbon Production from Ground Catering Waste Pyrolysis Coke - Nagy, Gábor; Simon, Andrea; Géber, Róbert; Rácz, Ádám (International Journal of Engineering and Management Sciences, 2019)
Three mixture of catering waste was pyrolyzed at 650, 725 and 900 °C and the solid residue (coke) was examined for powdered activated carbon production. For this, the carbon content, iodine number, particle size distribution and scanning electron microscopic images were analysed. Based on the carbon content, these cokes are suitable for activated carbon production, which were 60-85 wt.% (depending on the base material and pyrolysis temperature). The studied cokes showed slightly porous structure with smooth surfaces. Because of this, the iodine number was mostly small (13-30). Based on the grinding experiments, 10 minutes of grinding was found to be optimal. After this grinding time, the reached iodine number of powdered activated carbon was 350-610.